Analisis Lokasi Kawasan Kumuh dan Partisipasi Masyarakat di Kelurahan Suka Karya Kecamatan Kota Baru Jambi - Welly Yulfan Endin; Rosyani Rosyani; Harmes Harmes (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The urban problem in Jambi City is the extent of slum settlements. Based on the Decree of the Mayor of Jambi Number: 166 of 2016 concerning Determining the Location of Slum Housing and Slum Housing in Jambi City, it is known that there are 689.10 hectares of slums spread across 13 sub-districts and 5 sub-districts. Based on the Jambi Mayor's Decree, one of the sub-districts with slum settlements is Kota Baru District, which is located as the capital of the administrative area of Jambi City. The aims of this research are 1). Knowing the physical condition of the slum area in the Suka Karya sub-district, Kota Baru District, Jambi. 2.) Analyzing the Relationship between the Physical Environment and Community Participation in Suka Karya Village, Kota Baru District, Jambi. This type of mixed qualitative and quantitative research focuses on factual conditions in the field to determine scenarios for physical management and community participation in Suka Karya Village, Kota Baru District, Jambi. This type of quantitative research was used to determine the first and second objectives, while to determine the third research target a scenario model was developed from the results of the first and second studies. The study was conducted in 18 RTs in the Suka Karya Village, Kota Baru District, Jambi City. Data were analyzed using the slovin method. The research results show 1). The average results of the assessment of the physical condition of buildings, environmental roads, drinking water supply, environmental drainage, waste water management, waste management and fire protection conditions reached 14. According to the criteria for evaluating slum areas, Suka Karya Village is included in the Not Slum category. 2). Community participation in this location is included in the category of delegation of authority to the community in handling slum areas.